EVALUASI KEBIJAKAN PROGRAM KELUARGA HARAPAN (PKH) DALAM MENANGGULANGI KEMISKINAN DI KELURAHAN SUDAJAYA HILIR KOTA SUKABUMI - Arie Melani Purbasari (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
The Family Hope Program (PKH) is a social policy instrument initiated by the government to reduce poverty through a social assistance scheme. This study aims to evaluate the program in alleviating poverty in Sudajaya Hilir Village, Sukabumi City. The analytical framework refers to the concept of public policy evaluation proposed by Dunn (as cited in Subarsono, 2021, p. 126), which includes five dimensions: effectiveness, adequacy, equity, responsiveness, and appropriateness. This study employed a qualitative approach with a descriptive method through field observations, documentation, and in-depth interviews with five informants (individuals directly involved in and knowledgeable about the program implementation). The findings indicate that PKH has significantly contributed to improving community welfare. However, the community expressed dissatisfaction because the amount of assistance received was insufficient to meet family needs. In addition, staff members still lacked proficiency in the data updating process, there were unequal or inaccurate fund distributions (within the same category but with different nominal amounts, as well as categories that should have received assistance but did not), and unsynchronized data were still found between the data provided by the central government and the data validation stage. The findings of this study are expected to provide useful insights for the government regarding the implementation of the Family Hope Program (PKH) in poverty alleviation.